2018
DOI: 10.3390/dj6030024
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Study on the Effect of Amorphous Calcium Phosphate and Fluoride Solutions on Color Improvement of White Spot Lesions

Abstract: The ability of remineralizing agents to improve the color of white spot lesions (WSL) is an important aspect that should be investigated. The aim of this study was to evaluate the effects of 0.05% amorphous calcium phosphate (ACP), 0.5% ACP, and 0.05% fluoride solutions, as well as artificial saliva on the color improvement of white spot lesions (WSLs). In this in vitro study, 50 human premolar teeth were randomly classified into five groups. At baseline, all the samples were assessed by using a colorimeter (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…26 The L value reveals lightness, a value represents the position of red or green axes, and b value demonstrates the position of yellow or blue axes. 27 The color measurement system was made up of a spectrophotometer (PR-650 Spectra Scan, equipped with MS-75 and SL-0.5X lens;…”
Section: Surface Raman Intensity Mappingmentioning
confidence: 99%
“…26 The L value reveals lightness, a value represents the position of red or green axes, and b value demonstrates the position of yellow or blue axes. 27 The color measurement system was made up of a spectrophotometer (PR-650 Spectra Scan, equipped with MS-75 and SL-0.5X lens;…”
Section: Surface Raman Intensity Mappingmentioning
confidence: 99%
“…et al, who found that no significant difference in color improvement of white spot lesions between sodium fluoride and ACP. 15 This conflict might have resulted from application of ACP as mouthwash lacking casein, so the reaction was undermined by the rapid formation of calcium phosphate phase rather than diffusion into subsurface lesion when stabilized by casein.…”
Section: Discussionmentioning
confidence: 99%
“…Like any medical treatment, orthodontic treatment may have side effects such pain, root resorption, periodontal disease, temporomandibular dysfunction, caries, speech problems and enamel damage. [1][2][3][4][5] Pain is a common experience in orthodontic patients and is considered the most important factor deterring patient referral for further treatment. 6 Orthodontic pain arises from ischemia, inflammation, and edema in the compressed periodontal ligament.…”
Section: Introductionmentioning
confidence: 99%